2016
DOI: 10.1128/jvi.00694-16
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Human Astrovirus Capsid Protein

Abstract: Human astrovirus (HAstV) is a leading cause of viral diarrhea in infants and young children worldwide. HAstV is a nonenveloped virus with a T=3 capsid and a positive-sense RNA genome. The capsid protein (CP) of HAstV is synthesized as a 90-kDa precursor (VP90) that can be divided into three linear domains: a conserved N-terminal domain, a hypervariable domain, and an acidic C-terminal domain. Maturation of HAstV requires proteolytic processing of the astrovirus CP both inside and outside the host cell, resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 46 publications
0
41
0
Order By: Relevance
“…To identify the neutralization epitopes on the HAstV capsid, we first evaluated the capacity of the core and spike domains to induce total (determined by enzyme-linked immunosorbent assay [ELISA]) and neutralizing antibodies. These two structural domains of the virus can be produced in Escherichia coli in a soluble and correctly folded form (10)(11)(12)(13)(14). Rabbits and mice were immunized with either the purified, recombinant core or the spike domain of HAstV-1 (core1 or spike1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the neutralization epitopes on the HAstV capsid, we first evaluated the capacity of the core and spike domains to induce total (determined by enzyme-linked immunosorbent assay [ELISA]) and neutralizing antibodies. These two structural domains of the virus can be produced in Escherichia coli in a soluble and correctly folded form (10)(11)(12)(13)(14). Rabbits and mice were immunized with either the purified, recombinant core or the spike domain of HAstV-1 (core1 or spike1).…”
Section: Resultsmentioning
confidence: 99%
“…Cryo-electron microscopy of mature HAstV virions reveals particles of 44 nm comprised of a T ϭ 3 icosahedral shell and 30 globular spikes (9). The crystal structures of both VP34 (10,11) and VP25 (11)(12)(13)(14) have been recently determined; VP34 folds into a domain that constitutes the shell of the virus capsid (core domain), while VP27/VP25 form dimeric capsid spikes (spike domain). VP34 is derived from the highly conserved N-terminal region of VP70, while VP27/VP25, which differ only at their amino termini, are derived from the hypervariable region of VP70 (15).…”
mentioning
confidence: 99%
“…The TPMBQ ligand (guest) executed with various protein receptors (host) by molecular docking and it showed a strong interaction with all receptors (Figures ). This indicated to mutable capacity for the hydrogen bonding interaction by multi‐central groups internal docking complexes and all proteins have enter hydrogen bonding …”
Section: Resultsmentioning
confidence: 99%
“…Also it showed that the binding energy decreases upon coordination. So, the Co (II) complex was more active than HL ligand and could be used as very effective drug against gastroenteritis in the future …”
Section: Molecular Modeling Of Hl Ligand and Its [Co (Hl)(h2o)2cl2]3mentioning
confidence: 99%